Simplified Walking Simulation for Tuning a Passive Controllable Ankle Foot Orthosis - Dimas Adiputra (Telkom University, 2021)
A passive controllable ankle foot orthosis (PICAFO) has been developed to treat foot drop on post-stroke patient by controlling the walking gait passively. PICAFO controls the gait by utilizing a proportional integral (PI) controller with an ankle velocity reference. The PI controller must be tuned before being implemented on PICAFO. However, controller tuning based on experimental trial and error is not suggested since it requires the user to use the untuned PICAFO. Therefore, a simplified walking simulation is developed to tune the PI controller using Simulink of MATLAB software. The simulation mainly consists of several parts, such as PI controller, brake model, ankle torque to velocity transfer function, ankle velocity reference, and constant external torque. The result shows that the PI controller can be tuned accordingly to subject’s body mass index (BMI) and the brake model to meet the system specification. In this case, when the subject’s BMI is 22.2 and the brake maximum torque is 1.938 Nm, the system can control the ankle velocity with settling time less than 20 ms. However, if there is an external torque that is outside the range of brake capacities, then the system cannot do the control task. Therefore, improvement in the brake design is necessary in the future to achieve ankle velocity control within wide range of external torque.